Experimental investigation on fire resistance of CFST columns after earthquake. Issue 2 (1st September 2021) - Tan, Jike; Wang, Yuhang; Tang, Qi; Wang, Weiyong; Su, Meini
Abstract: Post‐earthquake fire is one of the most prone and dangerous disasters after earthquake. This study investigates the post‐earthquake fire performance of concrete‐filled steel tube (CFST) columns experimentally. An experimental program containing two parts has been carried out ‐ quasi‐static tests and fire tests. During the quasi‐static tests, four square CFST columns were loaded under constant compressive force and cyclic horizontal force, until reaching different degrees of seismic damage. Afterwards, the pre‐damaged columns were loaded under a constant axial compression ratio (i.e. ratio of the applied compressive load to its bearing capacity) of 0.3 at elevated temperatures. The fire resistance time and failure modes of these pre‐damaged CFST columns are reported herein. Local buckling occurred at the bottom of the specimens during the cyclic loading tests, while the mid‐height of the steel tube was found to be softened and buckled seriously during the high temperature tests. When columns reached the limit of fire resistance, their axial deformation increased rapidly. Results showed that pre‐seismic damage significantly affected the fire resistance of specimens – more serious pre‐damage resulted in lower fire resistance. The experimental results will be used to conduct parametric study and propose design rules for the fire performance of CFST columns with different degrees of seismic damage.